2018
DOI: 10.1111/pcmr.12684
|View full text |Cite
|
Sign up to set email alerts
|

Melasma, a photoaging disorder

Abstract: Summary Melasma is a common hyperpigmentary disorder. The impact on the quality of life of affected individuals is well demonstrated, demanding new therapeutic strategies. However, the treatment of melasma remains highly challenging. Melasma is often considered as the main consequence of female hormone stimulation on a predisposed genetic background. Although these two factors do contribute to this acquired pigmentary disorder, the last decade has revealed several other key players and brought new pieces to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
206
1
13

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 186 publications
(223 citation statements)
references
References 34 publications
3
206
1
13
Order By: Relevance
“…The increased number of spindle‐shaped p16 INK4A ‐positive fibroblasts is thought to originate from chronic UV irradiation. These findings are in line with the previous observations that melasma shows features of sun‐damaged skin and the in vitro UV‐induced senescence like phenotype of fibroblasts leads to the increased production of the melanogenic factors . The senescent cells were mainly observed in the upper layer of the dermis, which have the advantage of easy crosstalk with nearby melanocytes.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The increased number of spindle‐shaped p16 INK4A ‐positive fibroblasts is thought to originate from chronic UV irradiation. These findings are in line with the previous observations that melasma shows features of sun‐damaged skin and the in vitro UV‐induced senescence like phenotype of fibroblasts leads to the increased production of the melanogenic factors . The senescent cells were mainly observed in the upper layer of the dermis, which have the advantage of easy crosstalk with nearby melanocytes.…”
Section: Discussionsupporting
confidence: 91%
“…Immunohistochemical studies have shown that melasma shows prominent features of solar damaged skin compared with that in perilesional normal skin; lesional skin shows increased solar elastosis, vasculature and basement membrane disruption underlying increased epidermal pigmentation . These findings suggested in melasma skin, not only melanocytes but other actors, especially dermal components such as photoaged fibroblasts or vasculature, probably have a key role in the development and the relapses of melasma …”
Section: Introductionmentioning
confidence: 98%
“…When co‐cultured with sebocyte cell line, human epidermal melanocytes showed dendrites formation and altered melanogenesis . Several cytokines and growth factors, such as IL‐1α, IL‐6, angiopoietin and adipokine, released from sebocytes have been demonstrated to exert paracrine effects on epidermal melanocytes . The role of sebocytes with respect to the pathogenesis of melasma requires further investigation.…”
Section: Histopathologic Clues Of Melasma As a Photoaging Disordermentioning
confidence: 99%
“…Though generally regarded as a pigmentary disorder, recent evidence has demonstrated melasma to be a photoaging disorder . The histological findings of melasma are similar to photoaging and include solar elastosis, increased mast cells and sebaceous glands, as well as altered basal membranes and vascularization .…”
Section: Introductionmentioning
confidence: 99%